2022
DOI: 10.1055/s-0042-1745783
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Injections of Botulinum Toxin Type A in the Piglet Esophagus Is Safe and Feasible but Did Not Result in any Significant Structural Changes 3 Days after Injection

Abstract: Introduction Treatment for long-gap esophageal atresia (LGEA) aims at achieving primary anastomosis with minimal tension. Previous studies have shown that intramural injections with botulinum toxin type-A (BTX-A) from the adventitial side can increase the elongation of the piglet and rat esophagus before bursting, and that this effect is dose and time dependent. Our aim was to determine if endoscopic injections would be feasible, safe, and with an effect on the mechanical properties of the esophagus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…This may strongly impact the dose-effect curve and the timing of the effect. Furthermore, the effect of BoNT-A on the esophagus is currently controversial, as a recent publication of a piglet study showed no differences in the mechanical and histological characteristics of the esophagus in BoNT-A-injected piglets compared to controls [ 82 ].…”
Section: Therapeutic Applications In Veterinary Medicinementioning
confidence: 99%
“…This may strongly impact the dose-effect curve and the timing of the effect. Furthermore, the effect of BoNT-A on the esophagus is currently controversial, as a recent publication of a piglet study showed no differences in the mechanical and histological characteristics of the esophagus in BoNT-A-injected piglets compared to controls [ 82 ].…”
Section: Therapeutic Applications In Veterinary Medicinementioning
confidence: 99%
“…Furthermore, the effect of BoNT-A on the esophagus is controversial today, as a recent publication of a piglet study showed no differences in the mechanical and histological characteristics of the esophagus in BoNT-A-injected piglets compared to controls. [81].…”
mentioning
confidence: 99%